Entrepreneurship and potential of Universidad Nacional Mayor de San Marcos students - de Jesús Condori González, Andrea Teresa (2018)
The purpose of the following paper is to provide information on entrepreneurship situation in Latin America, starting from its internal variables, such as the average entrepreneur profile, to external variables that could directly affect the model. It also aims to increase the knowledge entrepreneurs should consider in order to realize their projects and increase their strengths and competitiveness. Finally, a study on a sample of students from the Universidad Nacional Mayor de San Marcos was conducted and analyzed in order to reveal student’s potential regarding entrepreneurship.